THE EFFECT ANALYSIS OF WORK EXPERIENCE AND WORK MOTIVATION ON WORK MOTIVATION AT PT. PELABUHAN INDONESIA IV (PERSERO) TARAKAN BRANCH, NORTH KALIMANTAN - s sutiyono; A Sriekaningsih; A Susanto; Achmad Daengs GS (Universitas 17 Agustus 1945 Surabaya, 2022)
The reason for this review was to examine the impact of work understanding and work inspiration on work inspiration at PT. Pelabukhan Indonesia IV (Persero) Tarakan branch, North Kalimantan. Likewise, the impact of work inspiration as an intermediate variable between understanding work and inspiration from working at PT. Pelabukhan Indonesia IV (Persero) Tarakan branch, North Kalimantan. The population in this center, as well as during the study, is mostly PT. Pelabuhan Indonesia IV (Persero) Tarakan branch with over 37 employees, including 1 chief supervisor, 5 boat directors and 31 employees. The logical procedure used is a path study using SPSS programming. The results showed that the work experience variable had a positive and critical impact on the work inspiration of the PT Pelabuhan Indonesia IV (Persero) Tarakan branch. Variable work experience has a positive and tremendous impact on the exhibitor's trade show.